2013
DOI: 10.1155/2013/241016
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide Embryopathy: An Enigmatic Challenge

Abstract: Thalidomide remains one of the world’s most notorious drugs due to the severe birth defects it induced in children between 1957 and 1962. Yet, to some this drug is a lifesaver, as it now enjoys renaissance in the treatment for a wide range of conditions including leprosy, multiple myeloma, Behcet’s disease, and some cancers. However, thalidomide has also been linked to causing a new generation of thalidomide survivors in Brazil, where the drug is used to treat leprosy. Surprisingly how thalidomide causes birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(113 citation statements)
references
References 180 publications
1
112
0
Order By: Relevance
“…Moreover, anti-angiogenic analogs of thalidomide cause teratogenic effects by inhibiting the growth of newly forming vessels (2, 3, 5). fli 1:EGFP zebrafish, which are known to be sensitive to teratogens (5, 27, 28), were used to assess the ability of Gu compounds to affect the development of the forming vasculature.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, anti-angiogenic analogs of thalidomide cause teratogenic effects by inhibiting the growth of newly forming vessels (2, 3, 5). fli 1:EGFP zebrafish, which are known to be sensitive to teratogens (5, 27, 28), were used to assess the ability of Gu compounds to affect the development of the forming vasculature.…”
Section: Resultsmentioning
confidence: 99%
“…Thalidomide exhibits anti-inflammatory actions (1-3) and its analog, lenalidomide, is known to be clinically effective in the treatment of multiple myeloma via its anti-inflammatory properties (35, 36). We therefore tested the Gu compounds to determine if they have an effect on the inflammatory response.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps surprisingly, thalidomide has little effect on rodent embryos, so research on its actions has necessarily been carried out on other organisms (Vargesson, 2013). Initial studies indicated that thalidomide is harmful to early chick embryos and injection into the yolk caused facial and spinal anomalies and shortening and stunting of the legs (Boylen et al, 1963).…”
Section: Studies In the Chick On Limb Deficiencies Produced By Thalidmentioning
confidence: 99%